"Observing and Analyzing" Images from a Simulated High-Redshift Universe. (4th January 2016) - Morgan, Robert J.; Windhorst, Rogier A.; Scannapieco, Evan; Thacker, Robert J.
Abstract: We investigate the high-redshift evolution of the rest-frame UV-luminosity function (LF) of galaxies via hydrodynamical cosmological simulations, coupled with an emulated observational astronomy pipeline that provides a direct comparison with observations. We do this by creating mock images and synthetic galaxy catalogs of ≈100 arcmin -2 fields from the numerical model at redshifts ≈4.5 to 10.4. We include the effects of dust extinction and the point-spread function (PSF) for the Hubble WFC3 camera for comparison with space observations. We also include the expected zodiacal background to predict its effect on space observations, including future missions such as the James Webb Space Telescope ( JWST ). When our model catalogs are fitted to Schechter function parameters, we predict that the faint-end slope (α) of the LF evolves as α = -1.16-0.12 z over the redshift range z  ≈ 4.5-7.7, in excellent agreement with observations from, e.g., Hathi and coworkers. However, for redshifts z  ≈ 6-10.4, α( z ) appears to display a shallower evolution, α = -1.79-0.03 z . Augmenting the simulations with more detailed physics—specifically stellar winds and supernovae (SN)—produces similar results. The model shows an overproduction of galaxies, especially at faint magnitudes, compared with the observations, although the discrepancy is reduced when dust extinction is taken into account.